Participatory Action Research (PAR) with LGBTQ+ & GNC youth in the United States: An interview with Michelle Fine, Maria Torre, and Allison Cabana. - Luciana Lobo Miranda (Revista de Psicologia)
Participatory Action Research (PAR) with LGBTQ+ & GNC youth in the United States: An interview with Michelle Fine, Maria Torre, and Allison Cabana.